IMPLEMENTATION OF THE INVESTMENT ACTIVITY REPORT (IAR) POLICY AT THE INVESTMENT ONE-STOP INTEGRATED SERVICES OFFICES OF PONTIANAK CITY - Yetty Yuniarti; Lina Sunyata; Fatmawati (RADJA PUBLIKA, 2025)
This thesis aims to provide an understanding of the implementation of the Investment Activity Report (IAR) policy at the Investment and One-Stop Integrated Services Office of Pontianak City. The research issues include the limited number of business actors submitting IAR, limited personnel in implementation, and the absence of strict sanctions for non-compliant business actors. These conditions have an impact on the released investment realization data being less than optimal. This study uses a qualitative method with Charles O. Jones's policy implementation theory, covering organizational, interpretation, and application aspects. The results of the study indicate obstacles in implementation, namely: organizational aspects, the number of human resources and infrastructure is inadequate; interpretation aspects, there has been no special socialization of IAR for business actors; application aspects, many business actors still do not submit IAR and sanctions have not reached all violators. Recommendations for this study include increasing human resources and infrastructure, increasing IAR socialization to business actors, and implementing rewards and punishments to encourage compliance.